A Transdermal Measurement Platform Based on Microfluidics. (25th December 2017) - Huang, Wen-Ying; Huang, Jung-Ping; Lin, Chia-Ching; Lin, Yung-Sheng
Abstract : The Franz diffusion cell is one of the most widely used devices to evaluate transdermal drug delivery. However, this static and nonflowing system has some limitations, such as a relatively large solution volume and skin area and the development of gas bubbles during sampling. To overcome these disadvantages, this study provides a proof of concept for miniaturizing models of transdermal delivery by using a microfluidic chip combined with a diffusion cell. The proposed diffusion microchip system requires only 80  μ L of sample solution and provides flow circulation. Two model compounds, Coomassie Brilliant Blue G-250 and potassium ferricyanide, were successfully tested for transdermal delivery experiments. The diffusion rate is high for a high sample concentration or a large membrane pore size. The developed diffusion microchip system, which is feasible, can be applied for transdermal measurement in the future.